1992
DOI: 10.1073/pnas.89.11.4845
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor soluble receptors circulate during experimental and clinical inflammation and can protect against excessive tumor necrosis factor alpha in vitro and in vivo.

Abstract: Tumor necrosis factor alpha (TNF alpha), a primary mediator of systemic responses to sepsis and infection, can be injurious to the organism when present in excessive quantities. Here we report that two types of naturally occurring soluble TNF receptors (sTNFR-I and sTNFR-II) circulate in human experimental endotoxemia and in critically ill patients and demonstrate that they neutralize TNF alpha-induced cytotoxicity and immunoreactivity in vitro. Utilizing immunoassays that discriminate between total sTNFR-I an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
428
5
16

Year Published

1993
1993
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 764 publications
(468 citation statements)
references
References 27 publications
19
428
5
16
Order By: Relevance
“…Girardin et al [29] have shown that the ratio of TNF-to sTNF-R in serum from patients with severe meningococcaemia correlated with clinical outcome. In addition, protective effects of sTNF-R in sepsis [34,35] and inhibitory effects of sTNF-R against pulmonary fibrosis in the animal model [36] have been demonstrated. These previous results indicated that sTNF-R may contribute to regulating TNF--mediated disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Girardin et al [29] have shown that the ratio of TNF-to sTNF-R in serum from patients with severe meningococcaemia correlated with clinical outcome. In addition, protective effects of sTNF-R in sepsis [34,35] and inhibitory effects of sTNF-R against pulmonary fibrosis in the animal model [36] have been demonstrated. These previous results indicated that sTNF-R may contribute to regulating TNF--mediated disease.…”
Section: Discussionmentioning
confidence: 99%
“…The elevation of sTNF-R in serum/plasma and biological fluids reflecting a variety of inflammatory disorders has been shown in several diseases [24][25][26][27][28][29][30][31]. In addition, the specific inhibitory effects of sTNF-R on TNF-activities [32,33], the protective effects of sTNF-R in animal models of sepsis [34,35] and the inhibitory effects of sTNF-R against the animal model of pulmonary fibrosis [36] have been shown. Although TNF-has been suggested to play a role in the pathogenesis of sarcoidosis, plasma levels of sTNF-R have not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, soluble isoforms of cell-surface receptors regulate receptor function in a number of biological systems (27,28). Fas and FasL proteins can also occur both as cell-surface and soluble proteins, with the soluble form of Fas (sFas) being generated by alternative mRNA splicing (29,30), whereas the soluble form of FasL (sFasL) is produced through the proteolytic cleavage of the membrane-bound receptor (31).…”
mentioning
confidence: 99%
“…The released receptors, in turn, depending on their concentration relative to that of TNF, have been proposed either to compete with their membrane-bound counterparts and limit TNF bioavailability (17) or to stabilize the ligand thus enhancing TNF signaling (18).…”
mentioning
confidence: 99%